Analisis Nilai Moral Dalam Cerita Rakyat Sendang Sani Pati - Fara Fatika Maharani; Putri Jenar Mahesa Ayu; Nur Kusuma Astuti; Mohammad Kanzunnudin (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to analyze the moral values ​​contained in the Sendang Sani story. This study used qualitative research methods. Regarding the data source, it comes from a book entitled